The Tetris model of resolving information needs within the information seeking process - Wilson, Max L. (2017)
Theoretical abstractions, of many different aspects of search, have played a crucial role in driving research into human information seeking and retrieval forward. From models of the Information Seeking Process, to how we perceive search systems, these models help us to 1) conceptually formalise and separate aspects of the model’s focus, 2) communicate more clearly about these aspects, 3) create hypotheses for subsequent research, and 4) produce implications for future systems. Implicit in these four aspects is that models and theories should have a focus and a purpose. After clarifying the relationships between models, theories, and meta-theories, this perspectives paper introduces the Tetris Model of Resolving Information Needs within the Information Seeking Process, the purpose of which is to better represent the behaviours around the Human Computer Interaction with Information Retrieval, which are often confounded within stage-based models of the Information Seeking Process. In particular, the possible sequence of actions performed by a searcher are typically linearly aligned from left-to-right, and thus imply a temporal progression. The differing focus of the Tetris model is to better capture the temporal experience of searching, by removing the implied progression of left-to-right. The aim of this perspectives paper, therefore, is to introduce this new Tetris Model, such that it can be used to formalise people’s interactive experiences in a new way, so that we can more clearly communicate about them, create hypotheses from the model, and consider novel design implications based upon it.